Effects of repeatedly heading a soccer ball on serum levels of two neurotrophic factors of brain tissue, BDNF and NGF, in professional soccer players - Bamac, B.; Tamer, G. S.; Colak, T.; Colak, E.; Seyrek, E.; Duman, C.; Colak, S.; Ozbek, A. (Biology of Sport, 2011)
The present study determined the effects of heading training on serum nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) levels in soccer players. Seventeen professional level male soccer players (mean ± SD), age 24 ± 4.4 years, were recruited from a 3rd league team. Each player completed 15 approved headings in about 20-25 minutes. Venous blood samples were obtained from soccer players before and after the heading training for analysis. Levels of NGF and BDNF in the serum were determined by a commercially available enzyme-linked immunosorbent assay (ELISA) kit. Mean ± SD serum NGF levels were 18.71 ± 3.36 pg·ml-1 before training and 31.41 ± 7.89 pg·ml-1 after training (p=0.000). Mean ± SD serum BDNF levels were 22.32± 3.62 pg·ml-1 before training and 55.41 ± 12.59 pg·ml-1 after training (p=0.000). In this study heading a soccer ball was found to cause an increase in serum concentrations of NGF and BDNF. We suggest that the microtrauma caused by repetitive heading and/or the course of survival of the injured neurons may lead to increased NGF and BDNF levels.